Adaptability in Buffaloes during Spring and Summer Seasons in Eastern Plane Zone of Uttar Pradesh, India - Rai, Vikas; Choudhary, Pankaj K.; Kumar, Pramod; Maurya, Pankaj K.; Maurya, Satyendra K.; Kumar, Abhishek; Kumar, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Adaptability of buffaloes during spring and summer seasons in three districts of eastern plane zone of Uttar Pradesh was studied bydifferent Heat tolerance indices like Ibrea heat tolerance coefficient (IHTC), Gaalaas heat tolerance test, Benezara coefficient of adaptabilityand Dairy search index. All parameters of heat tolerance indices were calculated by using different physiological parameters like rectaltemperature, pulse rate and respiration rate. Temperature humidity index (THI) of all three districts was also calculated by using drybulb temperature and humidity. There was a significant (p
Keywords: Adaptability; Dairy Search Index, Murrah buffaloes, Temperature Humidity Index